Interim Restorative Approach for the Management of Congenitally Missing Permanent Mandibular Incisors: Presentation of Three Cases - Prashanth Prakash; Jayadev M. Hallur; Rachana Narse Gowda (Case Reports in Dentistry)
Congenital missing of mandibular permanent incisors with retained primary incisors may jeopardize the esthetic appearance and psychological development of children, especially during the years of transition into adolescence. The retained primary teeth are necessary for the maintenance and normal development of alveolar bone, which in turn is essential for future definitive rehabilitation. In such situations, an interim restoration may be provided before any definitive treatment is given to comfort the young patient during this transition period. Interim restorations may include resin-modified additions to the existing teeth as well as more sophisticated restorations such as resin-retained bridge and removable partial dentures. However, this restoration differs for different clinical situations based on various factors such as age and patient compliance, and also consideration has to be given for the growth changes of the child. The aim of this present paper is to discuss the esthetic management of three cases with bilateral agenesis of permanent mandibular incisors and retained primary incisors with composite interim restoration.